Defining hard-to-reach populations for vaccination. Issue 37 (3rd September 2019) - Ozawa, Sachiko; Yemeke, Tatenda T.; Evans, Daniel R.; Pallas, Sarah E.; Wallace, Aaron S.; Lee, Bruce Y
Highlights: Hard-to-reach populations should not be defined based on vaccination outcome. A clear definition is needed to assess target population size and interventions. Hard-to-reach populations should be distinguished from hard-to-vaccinate populations. The literature poorly defines them without criteria or thresholds for classification. We propose definitions of hard-to-reach and hard-to-vaccinate populations. Abstract: Extending the benefits of vaccination to everyone who is eligible requires an understanding of which populations current vaccination efforts have struggled to reach. A clear definition of "hard-to-reach" populations – also known as high-risk or marginalized populations, or reaching the last mile – is essential for estimating the size of target groups, sharing lessons learned based on consistent definitions, and allocating resources appropriately. A literature review was conducted to determine what formal definitions of hard-to-reach populations exist and how they are being used, and to propose definitions to consider for future use. Overall, we found that (1) there is a need to distinguish populations that are hard to reach versus hard to vaccinate, and (2) the existing literature poorly defined these populations and clear criteria or thresholds for classifying them were missing. Based on this review, we propose that hard-to-reach populations be defined as those facing supply-side barriers to vaccination due to geography by distance or terrain, transient or nomadic movement, healthcare provider discrimination, lack of healthcare provider recommendations, inadequate vaccination systems, war and conflict, home births or other home-bound mobility limitations, or legal restrictions. Although multiple mechanisms may apply to the same population, supply-side barriers should be distinguished from demand-side barriers. Hard-to-vaccinate populations are defined as those who are reachable but difficult to vaccinate due to distrust, religious beliefs, lack of awareness of vaccine benefits and recommendations, poverty or low socioeconomic status, lack of time to access available vaccination services, or gender-based discrimination. Further work is needed to better define hard-to-reach populations and delineate them from populations that may be hard to vaccinate due to complex refusal reasons, improve measurement of the size and importance of their impact, and examine interventions related to overcoming barriers for each mechanism. This will enable policy makers, governments, donors, and the vaccine community to better plan interventions and allocate necessary resources to remove existing barriers to vaccination.